SiO2 / C composite material with multistage three-dimensional network structure as well as preparation method and application of SiO2 / C composite material
Through electrospinning technology combined with crosslinking reaction and carbonization treatment, SiO2/C composite material with a multi-stage three-dimensional network structure was prepared, which solved the problem of easy collapse and poor uniformity of carbon-based porous materials, achieved improvement of the structural integrity and conductivity of the material, and was suitable for electromagnetic wave absorption applications.
Patent Information
- Application Number
- CN202411868885.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Existing carbon-based porous materials are prone to collapse when subjected to external stress and have poor uniformity, making it difficult to ensure structural integrity and uniformity.
Electrospinning technology is used to combine SiO2 fiber felt with small molecule precursor solution, and SiO2/C composite material with a multi-stage three-dimensional network structure is prepared through cross-linking reaction and carbonization treatment. This method uses SiO2 fiber felt as a support and carbon nanotubes form a three-dimensional mesh structure to enhance the structural integrity and conductivity of the material.
The controlled growth of carbon materials is achieved, and the SiO2/C composite material with structural integrity and porosity characteristics is formed, which significantly improves the compressive resistance and uniformity of the material, and meets the needs of multiple reflections and scattering of electromagnetic waves.
Smart Images

Figure CN119707516A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon-based composite materials, and in particular relates to a SiO2 / C composite material with a multi-level three-dimensional network structure and a preparation method and application thereof. Background Art
[0002] Carbon-based porous materials are considered to be ideal electromagnetic wave absorbers due to their rich porosity, three-dimensional interconnected structure, excellent conductivity and good chemical stability. The rich porosity enables porous carbon materials to store a large amount of air, which can reduce the density of the absorber. However, traditional carbon-based porous materials are fragile and easily collapse when subjected to external stress, which limits their application. In addition, the structural regulation process of carbon-based porous materials is complex and its uniformity is difficult to ensure. Therefore, it is particularly important to suppress deformation and cracking under the action of external forces, prevent material collapse and ensure its uniformity. Summary of the invention
[0003] The purpose of the present invention is to solve the technical problems that existing carbon-based porous materials are prone to collapse under external forces and have poor uniformity, and to provide a SiO2 / C composite material with a multi-level three-dimensional network structure and a preparation method and application thereof.
[0004] One of the purposes of the present invention is to provide a method for preparing a SiO2 / C composite material having a multi-level three-dimensional network structure, the method being carried out according to the following steps:
[0005] S1: dissolving hexadecyltrimethylammonium bromide (CTAB) in SiO2 sol to form a precursor solution, then adding a spinning aid, stirring and mixing to obtain an electrospinning solution, and then preparing a SiO2 fiber felt containing CTAB by electrospinning;
[0006] S2: dissolving citric acid, ferric nitrate and cobalt nitrate in an ethanol solution to form a mixed solution, and then stirring the mixed solution with an ethanol solution of urea at room temperature to form a small molecule precursor solution;
[0007] S3: The SiO2 fiber felt containing CTAB is immersed in a small molecule precursor solution, and then heated for cross-linking reaction. After the reaction is completed, carbonization treatment is performed to obtain a SiO2 / C composite material.
[0008] It is further defined that the preparation of the SiO2 sol in S1 is as follows: tetraethoxysilane, ethanol, water and hydrochloric acid are mixed and then heated to condense and reflux for reaction to obtain a transparent solution, which is then continuously stirred under heating conditions until the residual volume is 50-70% of the original solution volume to obtain a SiO2 sol.
[0009] It is further defined that the molar ratio of tetraethoxysilane, ethanol, water and hydrochloric acid is 1:(2-4):(0.5-1.5):(6×10-4 -8×10 -4 ).
[0010] It is further defined that the condensation reflux reaction temperature is 70-80°C and the time is 5-7h.
[0011] Further defined, stirring is continued at 80-90°C.
[0012] It is further defined that the CTAB concentration in the precursor solution in S1 is 25-50 mg / mL.
[0013] It is further defined that the spinning aid in S1 is polyethylene oxide, and the added amount is 0.1-0.3% of the mass of the precursor solution.
[0014] It is further defined that the electrospinning parameters in S1 are: feed rate of 0.5-1.5 mL / h, acceleration voltage of 15-25 kV, and distance between the injection needle tip and the collector of 10-20 cm.
[0015] It is further defined that the molar ratio of citric acid, ferric nitrate and cobalt nitrate in S2 is (4-6):(1.5-2.5):1.
[0016] It is further defined that the concentration of citric acid in the mixed solution in S2 is 0.5-1.5 mol / L.
[0017] It is further defined that the volume ratio of ethanol to water in the mixed solution in S2 is (2-3):1.
[0018] It is further defined that the urea concentration in the ethanol aqueous solution of urea in S2 is 6-8 mol / L.
[0019] It is further defined that the volume ratio of ethanol to water in the ethanol-water solution of urea in S2 is (2-3):1.
[0020] It is further defined that the molar ratio of urea to citric acid in S2 is (6-7):1.
[0021] It is further defined that the cross-linking reaction temperature in S3 is 170-190°C and the time is 10-20h.
[0022] It is further defined that the carbonization temperature in S3 is 800-1200°C, the time is 0.5-1.5h, and the heating rate is 4-6°C / min.
[0023] The second object of the present invention is to provide a SiO2 / C composite material prepared by the above method, in which the SiO2 fiber felt serves as a support and the three-dimensional network structure porous carbon formed by interconnected carbon nanotubes is filled in the support.
[0024] It is further defined that the diameter of the carbon nanotube is 1-5nm, the diameter of the three-dimensional network structure porous carbon mesh is 10-50nm, the diameter of the SiO2 fiber in the SiO2 fiber felt is 300-800nm, and the porosity is 80-99.
[0025] It is further defined that the volume proportion of carbon material in the SiO2 / C composite material is 80-95%.
[0026] The third object of the present invention is to provide an application of the SiO2 / C composite material prepared by the above method in electromagnetic wave absorption.
[0027] Compared with the prior art, the present invention has the following significant effects:
[0028] The present invention uses SiO2 fiber as a support, and introduces CTAB to adjust the carbon structure produced by the small molecule cross-linking reaction. In order to ensure the dispersibility of CTAB in the system, CTAB is introduced into the SiO2 fiber by using electrostatic spinning technology, and the SiO2 fiber slowly releases CTAB in the small molecule cross-linking reaction system, and a cross-linked porous carbon material is prepared on a one-dimensional SiO2 nanofiber, so as to ensure the dispersibility of CTAB in the system. The abundant Si-OH groups on the surface of the SiO2 fiber ensure that the CTAB part is widely combined on the entire SiO2 fiber. The presence of CTAB guides the carbon nanomaterial to grow along the SiO2 fiber as a support, and finally forms a SiO2 / C composite material. The method of the present invention realizes the controllable growth of carbon material, thereby forming a new composite material with structural integrity and carbon network structure, which is used as an absorbing material to meet the needs of the absorbing material for multiple reflections and scattering of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The macroscopic digital photos and morphological SEM images of the materials obtained in Example 1 and Comparative Examples 1-2; (a), (d) correspond to Comparative Example 1; (b), (e) correspond to Comparative Example 2; (c), (f) correspond to Example 1;
[0030] Figure 2 The macroscopic morphology and local magnified image of the SiO2 / C composite material obtained in Example 1; (a) - macroscopic morphology; (b) - magnified image of the local position in Figure (a); (c) - force response mechanism of the SiO2 / C composite material;
[0031] Figure 3 SEM images of the SiO2 / C composite material prepared in Example 1 at different magnifications; (a) -5k magnification (b) -10k magnification;
[0032] Figure 4TEM image of the SiO2 / C composite material prepared in Example 1; (b) is an enlarged view of a local position in (a);
[0033] Figure 5 Characterization diagram of the wave absorption performance of the SiO2 / C composite material prepared in Example 1; (a) - reflection loss curve diagram; (b) - reflection loss three-dimensional diagram. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0036] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0037] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.
[0038] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0039] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0041] Embodiment 1: The preparation method of the SiO2 / C composite material having a multi-level three-dimensional network structure in this embodiment is carried out according to the following steps:
[0042] (1) Preparation of SiO2 sol
[0043] Tetraethoxysilane, ethanol, water and hydrochloric acid were mixed in a ratio of 1:3:1:7×10 -4 The mixture was uniformly mixed in a molar ratio of 1:1 and then condensed and refluxed at 75°C for 6 hours to obtain a transparent solution. The transparent solution was continuously stirred at 85°C until the residual volume was 60% of the original solution, thereby preparing a uniform SiO2 sol.
[0044] (2) Preparation of SiO2 electrospinning precursor containing CTAB
[0045] CTAB was added to the SiO2 sol, completely dissolved and stirred at room temperature for 3 hours to prepare a precursor solution with a CTAB content of 50 mg / mL. Thereafter, 0.2 wt% polyethylene oxide was added to the precursor solution as a spinning aid and stirred at room temperature for 1 hour to obtain an electrospinning solution.
[0046] (3) Electrospinning process
[0047] The electrospinning solution was placed in a 10 mL syringe, and the injection needle (with an inner diameter of 6 mm) was connected to the positive electrode of the high voltage power supply, and the metal plate connected to the negative electrode of the high voltage power supply was used as the receiving end for electrospinning. The parameters of electrospinning were: the feed rate was 1 mL / h, the acceleration voltage was 20 kV, and the distance between the tip of the injection needle and the collector was 15 cm. The SiO2 fiber mat containing CTAB was obtained, wherein the SiO2 fiber diameter was 800 nm and the thickness was 20 mm.
[0048] (4) Preparation of small molecule cross-linking reaction precursors
[0049] Take 3.5mL of deionized water and mix it with 7.5mL of ethanol, add 12mmol of citric acid, 5mmol of ferric nitrate and 2.5mmol of cobalt nitrate, completely dissolve at room temperature and stir for 1h to form solution A. Use the same method to completely dissolve 80mmol of urea in a mixed solution of 3.5mL of deionized water and 7.5mL of ethanol to obtain solution B. Mix solution A and solution B and stir continuously at room temperature for 3h to form a small molecule precursor solution with uniform component distribution.
[0050] (5) Small molecule cross-linking reaction process
[0051] The SiO2 fiber felt containing CTAB was soaked in the small molecule precursor solution, and then placed in a closed container and kept in an oven at 180°C in an air atmosphere for 15 hours. During this stage, the citric acid and urea metal complexes simultaneously underwent solvent evaporation and cross-linking reactions.
[0052] (6) Carbonization stage
[0053] The obtained small molecule cross-linked product was placed in a tube furnace and treated at 1000°C in a nitrogen atmosphere for 1 hour with a heating rate of 5°C / min to remove the carbon structure and residual organic matter in SiO2, and obtain a SiO2 / C composite material with a multi-level three-dimensional network structure. The volume proportion of carbon material in the obtained SiO2 / C composite material is 85%.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that steps (1) to (3) are omitted, and the small molecule precursor solution obtained in step (4) is directly subjected to the crosslinking reaction in step (5) and the carbonization treatment in step (6) to obtain a pure carbon material. The other steps and parameters are the same as those in Example 1.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 is that CTAB in step (2) is omitted to obtain a SiO2 / C composite material. The other steps and parameters are the same as those in Example 1.
[0058] The morphology of the materials obtained in Example 1 and Comparative Examples 1-2 was characterized. The results are as follows: Figure 1 As shown in Figure 1(a), it can be seen that in the absence of SiO2 nanofiber carriers, the product of small molecule cross-linking is mainly composed of flaky carbon materials. Due to the aggregation of reactants in the small molecule cross-linking stage, the resulting product does not appear in the form of an integral structure. Figure 1 As shown in the SEM image in (d), the microscopic morphology shows that in the absence of CTAB, the carbon material forms a dense layered structure and cannot produce a porous structure.
[0059] from Figure 1 (b) It can be seen that due to the support of SiO2 nanofibers in the material, it forms a unified structure. However, the lack of CTAB in the system causes the carbon material to aggregate into a dense block structure. Figure 1 This observation is further confirmed by the SEM image in (e), which shows densely packed carbon materials aggregated near the SiO2 nanofibers.
[0060] from Figure 1 As can be seen in (c), the macroscopic morphology of the sample supported by CTAB-SiO2 fibers after the cross-linking stage shows that the carbon structure fills the gaps between the supports without excessive aggregation, as the SiO2 fibers act as supports. Therefore, the obtained product presents a monolithic structure. Figure 1 This is further confirmed by the SEM image in (f). In the SEM image, it can be observed that the carbon material grows around the SiO2 fibers, forming a porous structure due to the action of free CTAB in the solution. In summary, the electrospun SiO2 nanofibers can be used as a support to support the overall structure of the composite material to form a single component with a complete structure, rather than a powdered structure. In addition, the structure of the carbon material is regulated by CTAB to meet the needs of the absorbing material for multiple reflections and scattering of electromagnetic waves.
[0061] The macroscopic morphology and partial enlarged image of the SiO2 / C composite material with a multi-level three-dimensional network structure obtained in Example 1 of the present invention are shown in FIG. Figure 2 As shown in the figure, the sample shows a layered structure due to the SiO2 fiber felt as a support and the porous carbon material filled in the structure. This layered structure has an excellent response mechanism to external pressure. Rebound is a phenomenon caused by elastic recovery after unloading. When external pressure is applied to the layered structure, the structure undergoes elastic deformation in response to the external pressure. In this process, energy is stored in the structure in the form of potential energy through the twisting and stretching of the bonds. As the external pressure decreases or disappears, the energy stored in the structure begins to release. The layered structure rebounds, releasing the stored energy, causing the structure to gradually return to its original shape. The whole process is dynamic and continues until equilibrium is reached. This energy storage and release mechanism gives the layered structure elasticity, allowing it to quickly return to its original state and release the stored energy when subjected to pressure.
[0062] The SEM images of the SiO2 / C composite material with a multi-level three-dimensional network structure obtained in Example 1 of the present invention at different magnifications are as follows: Figure 3 As shown, TEM Figure 4As shown, it can be observed in the transmission electron microscope image that the diameter of the silica fiber is about 800nm, and the porous carbon on its surface exists in the form of a tubular structure interconnected into a three-dimensional network with a diameter of about 3-5nm, which means that the SiO2 / C composite material with SiO2 fiber as the support has a multi-level structure, and its carbon material structure is a three-dimensional network structure built by carbon nanotubes.
[0063] Application Examples
[0064] The SiO2 / C composite material with a multi-level three-dimensional network structure obtained in Example 1 was uniformly mixed with molten paraffin at a mass ratio of 20:80, and pressed to form a ring-shaped wave absorbing test sample. The inner diameter of the ring body was 3 mm, the outer diameter was 7 mm, and the thickness was 2 mm±5%.
[0065] Conduct electromagnetic wave absorption test, the results are as follows Figure 5 As shown in the figure, its maximum reflection loss still shows the minimum reflection loss at around 14GHz. At this frequency, the reflection loss of 7.5mm thickness can reach a minimum of -37.8dB. The introduction of CTAB promotes the formation of a three-dimensional conductive network, resulting in continuous and rapid transport of carriers inside the material. In this process, Joule heat is generated and dissipated, resulting in enhanced conductivity loss.
[0066] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a SiO2 / C composite material having a multi-level three-dimensional network structure, characterized in that: The method: S1: dissolving CTAB in SiO2 sol to form a precursor solution, then adding a spinning aid, stirring and mixing to obtain an electrospinning solution, and then preparing a SiO2 fiber felt containing CTAB by electrospinning; S2: dissolving citric acid, ferric nitrate and cobalt nitrate in an ethanol solution to form a mixed solution, and then stirring the mixed solution with an ethanol solution of urea at room temperature to form a small molecule precursor solution; S3: The SiO2 fiber felt containing CTAB is immersed in a small molecule precursor solution, and then heated for cross-linking reaction. After the reaction is completed, carbonization treatment is performed to obtain a SiO2 / C composite material.
2. The method according to claim 1, characterized in that Preparation of SiO2 sol in S1: Tetraethoxysilane, ethanol, water and hydrochloric acid are mixed and heated to condense and reflux to react to obtain a transparent solution, which is then continuously stirred under heating conditions until the residual volume is 50-70% of the original solution volume to obtain SiO2 sol.
3. The method according to claim 2, characterized in that The condensation reflux reaction temperature is 70-80°C, the time is 5-7h, and stirring is continued at 80-90°C.
4. The method according to claim 1, characterized in that The CTAB concentration in the precursor solution in S1 was 25-50 mg / mL, and the electrospinning parameters were: feed rate was 0.5-1.5 mL / h, acceleration voltage was 15-25 kV, and the distance between the injection needle tip and the collector was 10-20 cm.
5. The method according to claim 1, characterized in that The molar ratio of citric acid, ferric nitrate and cobalt nitrate in S2 is (4-6):(1.5-2.5):1, and the concentration of citric acid in the mixed solution is 0.5-1.5 mol / L.
6. The method according to claim 1, characterized in that The urea concentration in the ethanol aqueous solution of urea in S2 is 6-8 mol / L, and the molar ratio of urea to citric acid is (6-7):
1.
7. The method according to claim 1, characterized in that In S3, the cross-linking reaction temperature is 170-190°C, the time is 10-20h, the carbonization temperature is 800-1200°C, the time is 0.5-1.5h, and the heating rate is 4-6°C / min.
8. The SiO2 / C composite material obtained by the method according to any one of claims 1 to 7, characterized in that: In the composite material, SiO2 fiber felt is used as a support, and porous carbon with a three-dimensional network structure formed by interconnected carbon nanotubes is filled in the support.
9. The composite material according to claim 8, characterized in that The diameter of carbon nanotubes is 1-5nm, the diameter of porous carbon mesh in three-dimensional network structure is 10-50nm, the diameter of SiO2 fibers in SiO2 fiber felt is 300-800nm, the porosity is 80-99, and the volume proportion of carbon material in SiO2 / C composite material is 80-95%.
10. Use of the SiO2 / C composite material according to claim 9 in electromagnetic wave absorption.
Citation Information
Patent Citations
Preparation technology of carbon nanofiber composite silicon dioxide aerogel
CN105418052A
Preparation method of thermo-sensitive mesoporous carbon nanotube composite fiber-nano-silica gel
CN107433171A
Preparation method of ferroferric oxide / silicon dioxide composite fiber wave-absorbing material
CN110042500A
Elastic ceramic micro-nanofiber aerogel thermal insulation material as well as preparation method and application thereof
CN117902884A
Three-dimensional ordered porous carbon / manganese oxide composite wave-absorbing material as well as preparation method and application thereof
CN119060690A
Cited By
Preparation method of FeCo (SiO2 / C) film and wave-absorbing, heat-insulating and anti-corrosion application of FeCo (SiO2 / C) film
CN120591959A